Yam Semi-Autotrophic Hydroponic (SAH) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Building Sustainable Yam Seed Value Chain, Yam Semi-Autotrophic Hydroponic (SAH)